Elaboración e implementación del curso virtual de moodle para los docentes del colegio nacional “26 de Noviembre” de la ciudad de Zaruma, periodo 2013-2014 - Zambrano Toro, Manuel Ambrocio (2014)
The educational institutions of the country are required to make educational reforms and changes in its infrastructure in order to improve every day teaches the process of learning ; National College " November 26 " , has classrooms with technological equipment but lacks a virtual learning environment ; I have decided to make the development and implementation of a virtual course for teachers. This work was conducted in Region 7 of the province of El Oro, Canton Zaruma , Urbana Zaruma parish , at the National College November 26 , located at Av Honorato Márquez. The interview was aimed at teaching and structured in the same 5 questions aimed at gathering information on topics covered in the online course. It was possible that teachers design teaching resources based on schedules and established formats for each of the subjects , implementing the chords online courses to the needs of students achieving meaningful learning of topics covered in the classroom , making a didactic support especially for students with learning disabilities.